Syntactic Behavior of Verbs in Bima Language - Rabiyatul Adawiyah; Bukhori Muslim; Lukman Lukman (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2023)
This research was conducted to determine the syntactic behavior of Verbs in the Bima language. The analytical method used in this study is a qualitative descriptive method that describes data in the form of words or sentences containing verbs in the Bima language. The research locations were conducted in several villages in Bima Regency and Bima City. Data collection was carried out using introspection, listening, and speaking methods. The result of the research is that the syntax behavior of the Bima language verbs in this study is adapted to the structural environment. Data found related to how the behavior of verbs in their syntactic construction. The forms of verbs in the syntactic behavior referred to are transitive verbs and intransitive verbs. Intransitive verbs are analyzed based on whether or not there is an object that will follow the verb. If a verb can have a complete meaning without the presence of an object, it is declared as an intransitive verb. On the other hand, if a verb has a complete meaning and must be followed by an object, then it is stated as a transitive verb. In the Bima language, many transitive verbs are dominated by words with affixes. Many intransitive verbs are dominated by prefixes ka, ma, na, ta, da, di, ra and endings ku, mu, na, ta, ja, si, ro, ra, du, ni, pu, and mpa.